A DEVELOPMENT OF FLIP BOOKMAKER BASED MODULE AS A SUPPORT OF E-LEARNING IN SENIOR HIGH SCHOOL - Farida Nurlaila; Vandalita MM Rambitan; Sukartiningsih (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The progress of science and technology in the era of globalization, especially the era of the industrial revolution 4.0, Affected the use of the internet in the learning process. Conventional learning begins to be integrated with electronic learning or e-learning so that students can learn anytime and anywhere. The purpose of this study is to produce a learning media e-module based on flip bookmakers that is feasible and effective for use in biology subjects at Samarinda City Public High School. The research method follows the Borg and Gall development procedure with 4 main stages, namely 1) pre-development 2) initial development 3) development 4) application. The results showed that the flip book-based e-module media in biology in Samarinda City High School got an average score of 89.26%, included in the very valid category. The response of students got an assessment of 82.21% included in the very good category. This shows that the e-modules produced are suitable for use in learning. From the pretest and posttest, the gain score is 0.75 in the high category, and the students' score is more than 80% above the KKM, proving the use of e-modules is very effective in learning.